2018
DOI: 10.1038/s41598-018-34170-8
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Clinical Manifestations and Ophthalmic Outcomes of Ocular Syphilis at a Time of Re-Emergence of the Systemic Infection

Abstract: This Article contains an error in the Methods section. "(2) an abnormal CSF (i.e. reactive VDRL and/or greater than 4 leukocytes/mm 3 and protein concentration less than 40 mg/dl);" should read: "(2) an abnormal CSF (i.e reactive VDRL and/or greater than 4 leukocytes/mm 3 and protein concentration greater than 40 mg/dl);"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our study, the most common form of uveitis among patients with ocular syphilis was non-granulomatous anterior uveitis followed by posterior involvement. However, among the 129 patients in the previously mentioned study by Furtado et al [24] found that posterior uveitis accounts for the majority of cases of ocular syphilis most commonly posterior placoid chorioretinitis and syphilitic punctate inner retinitis. Another study from France also found most patients to be mostly posterior placoid chorioretinitis [29] .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, the most common form of uveitis among patients with ocular syphilis was non-granulomatous anterior uveitis followed by posterior involvement. However, among the 129 patients in the previously mentioned study by Furtado et al [24] found that posterior uveitis accounts for the majority of cases of ocular syphilis most commonly posterior placoid chorioretinitis and syphilitic punctate inner retinitis. Another study from France also found most patients to be mostly posterior placoid chorioretinitis [29] .…”
Section: Resultsmentioning
confidence: 95%
“…In our study, 11/53 (20.75%) had poor visual outcomes with vision less than 20/400, with 7/11 (63.64%) of those with posterior involvement. However, a study by Furtado et al [24] found most patients to have visual acuity of 20/50 or worse, and had posterior involvement.…”
Section: Resultsmentioning
confidence: 97%